Dyskurs wegański i wegetariański a szowinizm gatunkowy w memach internetowych - Woźniak, Anna (Zoophilologica. Polish Journal of Animal Studies, 2016)
The Internet is one of the most important inventions of the 20th century. The virtualization of social life is a growing process. In this article the author examines memes via vegan and vegetarian perspectives to analyze how speciesism occurs in them.